The Impact of Cefr-Aligned Curriculum on Year2 Intermediate Pupils’ Lbi Reading Screening - Kamarrudin, Mastempawan Binti; Binti Mohamad, Maslawati (Opción, 2019)
This study will investigate the impact of CEFR-aligned English Language curriculum on Literacy and Numeracy Screening (LINUS) particularly reading screening. This study was conducted with 3 English teachers and 61 Year 2 intermediate pupils from an urban school in Melaka. The data was collected via pre-test, post-test, questionnaire and interview. The results showed the positive impact of the new curriculum on pupils’ reading screening compared to the use of the previous curriculum. Therefore, it is hoped that the new curriculum will help to improve the reading skills of the pupils thoroughly in ESL classroom.